RADIAL PULSATILE MASS — APPEARANCES CAN BE DECEIVING - Semião, Ana Carolina (2021)
Adventitial cystic disease (ACD) is a rare condition. It affects mostly the popliteal artery, with few cases reported affecting the radial artery. This condition is characterized by accumulation of mucinous content at the adventitious layer.